Bentuk dan Fungsi Kata Umpatan Mengakrabkan Suasana di Kalangan Mahasiswa - Lida Helmiyanti (IKIP Siliwangi, 2020)
Swear words are woreds that are spoken when the speaker is in an emotional, condition, swear words usually have a negative meaning. However, in thid study swear words no longer have a negative meaning if the speaker and the interlocutor are close. In this study, the researcher investigate swear words come from Sundanese. This study aims to determine the from and function of swear words to familiarize the atmosphere used by the students of IKIP Siliwangi. The research subjects wareclass B4 2016 students of Indonesian Language Study Program of IKIP Siliwangi. Describing the from and functio of swear words that are commonly used by college students is no longer a taboo thing, because basically they say swear words is only for greeting and their way of making the conversation not stiff but rather build intimacy and closeness between friends. The method used in this study is descriptive qualitative method. Data collection was done by listening to collage and field observation. Based on the study results of the study, it can be concluded that there are two forms of swear words used by collage students of IKIP Siliwangi students, (1) reference swear words from a spirit and (2) references to one’s mental condition. The funcion of swear words that exist among college students is merely to familiarize the atmosphere when they are in a conversation.